Coagulation factor XII induces pro-inflammatory cytokine responses in macrophages and promotes atherosclerosis in mice - Vorlova, Sandra; Koch, Miriam; Manthey, Helga D.; Cochain, Clement; Busch, Martin; Chaudhari, Sweena M.; Stegner, David; Yepes, Manuel; Lorenz, Kristina; Nolte, Marc W.; Nieswandt, Bernhard; Zernecke, Alma (Thrombosis and Haemostasis, 2017)
Atherosclerosis is considered a chronic inflammatory disease of the vessel wall. Coagulation pathways and immune responses contribute to disease development. The role of coagulation factor XII (FXII) in vascular inflammation, however, remains controversial. We here investigated the function of FXII in atherosclerosis using apolipoprotein E and FXII-deficient (F12−/−Apoe−/−) mice. Compared to F12+/+Apoe−/− controls, atherosclerotic lesion formation was reduced in F12−/−Apoe−/− mice. This was associated with a decrease in serum interleukin (IL)-1β and IL-12 levels and reduced expression of pro-inflammatory cytokines in the aorta in atherosclerotic F12−/−Apoe−/− mice, as well as diminished Th1-cell differentiation in the aorta, blood, and lymphoid organs. No changes in circulating bradykinin, thrombin-antithrombin-complexes or plasminogen were observed. Mechanistically, activated FXII (FXIIa) was revealed to directly induce bone marrow-derived macrophages to secrete pro-inflammatory cytokines, including tumour necrosis factor-α, IL-1β, IL-12, and IL-6. Exposure of bone marrow-derived antigen presenting cells to FXIIa similarly induced pro-inflammatory cytokines, and an enhanced capacity to trigger antigen-specific interferon γ-production in CD4+ T cells. Notably, bone-marrow derived macrophages were capable of directly activating FXII. Moreover, the induction of cytokine expression by FXIIa in macrophages occurred independently of FXII protease enzymatic activity and was decreased upon phospholipase C treatment, suggesting urokinase-type plasminogen activator receptor (uPAR) to confer FXIIa-induced cell signalling. These data reveal FXII to play an important role in atherosclerotic lesion formation by functioning as a strong inducer of pro-inflammatory cytokines in antigen-presenting cells. Targeting of FXII may thus be a promising approach for treating cardiovascular disease.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atherosclerosis; inflammation; coagulation factor; cytokine; macrophage